Arterial hypertension: ambulatory patients’ point of view. First results of GARANT Study - S. A. Shalnova; A. D. Deev; O. V. Vikhireva (Кардиоваскулярная терапия и профилактика)
Aim. To study patients’ awareness on arterial hypertension (AH), its treatment and prevention, as well as to investigate AH therapy compliance, the GARANT Study (PharmacoepidemioloGy of ARteriAl HyperteNsion in Real-World Ambulatory PracTice) was performed, supported by KRKA company. Material and methods. Doctors and patients from 99 clinics in 63 Russian cities participated in the study. In total, 9214 patients (3189 men, 6025 women; mean age 54,7 years) responded to this doctor-performed survey. Results. AH awareness was high enough, with as many as 86,8% of the patients knowing their blood pressure (BP) level. At the same time, only every third participant knew his or her cholesterol (CH) level. More than 70% of men and 80% of women knew that AH is a risk factor (RF). From the patients’ point of view, AH was the leading RF. Awareness on the other RF was below 33%, with only two exceptions: alcohol (42,2% for men, 35,8% for women) and smoking (38,4% and 30,9%, respectively). Conclusion. While doctors are fully responsible for high BP diagnostics and explanation of pharmaceutical and non-pharmaceutical therapy benefits and risks to their patients, treatment compliance and lifestyle modification should be supported by patients themselves, their families, and society as a whole.